Proteolytic degradation of neuropeptide Y (NPY) from head to toe: Identification of novel NPY-cleaving peptidases and potential drug interactions in CNS and Periphery - Wagner, Leona; Wolf, Raik; Zeitschel, Ulrike; Rossner, Steffen; Petersen, Asa; Leavitt, Blair R.; Kaestner, Florian; Rothermundt, Matthias; Gaertner, Ulf-Torsten; Guendel, Daniel; Schlenzig, Dagmar; Frerker, Nadine; et al. (Journal of Neurochemistry, 2015)
The bioactivity of neuropeptide Y (NPY) is either N-terminally modulated with respect to receptor selectivity by dipeptidyl peptidase 4 (DP4)-like enzymes or proteolytic degraded by neprilysin or meprins, thereby abrogating signal transduction. However, neither the subcellular nor the compartmental differentiation of these regulatory mechanisms is fully understood. Using mass spectrometry, selective inhibitors and histochemistry, studies across various cell types, body fluids, and tissues revealed that most frequently DP4-like enzymes, aminopeptidases P, secreted meprin-A (Mep-A), and cathepsin D (CTSD) rapidly hydrolyze NPY, depending on the cell type and tissue under study. Novel degradation of NPY by cathepsins B, D, L, G, S, and tissue kallikrein could also be identified. The expression of DP4, CTSD, and Mep-A at the median eminence indicates that the bioactivity of NPY is regulated by peptidases at the interphase between the periphery and the CNS. Detailed ex vivo studies on human sera and CSF samples recognized CTSD as the major NPY-cleaving enzyme in the CSF, whereas an additional C-terminal truncation by angiotensin-converting enzyme could be detected in serum. The latter finding hints to potential drug interaction between antidiabetic DP4 inhibitors and anti-hypertensive angiotensin-converting enzyme inhibitors, while it ablates suspected hypertensive side effects of only antidiabetic DP4-inhibitors application. The bioactivity of neuropeptide Y (NPY) is either N-terminally modulated with respect to receptor selectivity by dipeptidyl peptidase 4 (DP4)-like enzymes or proteolytic degraded by neprilysin or meprins, thereby abrogating signal transduction. However, neither the subcellular nor the compartmental differentiation of these regulatory mechanisms is fully understood. Using mass spectrometry, selective inhibitors and histochemistry, studies across various cell types, body fluids, and tissues revealed that most frequently DP4-like enzymes, aminopeptidases P, secreted meprin-A (Mep-A), and cathepsin D (CTSD) rapidly hydrolyze NPY, depending on the cell type and tissue under study. Novel degradation of NPY by cathepsins B, D, L, G, S, and tissue kallikrein could also be identified. The expression of DP4, CTSD, and Mep-A at the median eminence indicates that the bioactivity of NPY is regulated by peptidases at the interphase between the periphery and the CNS. Detailed ex vivo studies on human sera and CSF samples recognized CTSD as the major NPY-cleaving enzyme in the CSF, whereas an additional C-terminal truncation by angiotensin-converting enzyme could be detected in serum. The latter finding hints to potential drug interaction between antidiabetic DP4 inhibitors and anti-hypertensive angiotensin-converting enzyme inhibitors, while it ablates suspected hypertensive side effects of only antidiabetic DP4-inhibitors application.
EVALuna2:24982